2017
DOI: 10.1111/desc.12612
|View full text |Cite
|
Sign up to set email alerts
|

Children prenatally exposed to maternal anxiety devote more attentional resources to neutral pictures

Abstract: Maternal anxiety during pregnancy can negatively affect fetal neurodevelopment, predisposing the offspring to a higher risk of behavioral and emotional problems later in life. The current study investigates the association between maternal anxiety during pregnancy and child affective picture processing using event-related brain potentials (ERPs). Mothers reported anxiety during the second trimester using the anxiety subscale of the Symptom Checklist (SCL-90). At age 4 years, child affective picture processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The earliest predictors of child sleep disturbance can potentially be found in utero. Given that child hypervigilance and hyper-arousal are associated with prenatal stress exposure 9 12 , it follows that prenatal exposure to maternal stress and negative affect may be a risk factor for the development of early sleep problems. Indeed, a small number of studies have begun to provide evidence for this linkage, reporting sleep problems in children prenatally exposed to maternal mood disturbance 13 , 14 and later links to adult insomnia 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The earliest predictors of child sleep disturbance can potentially be found in utero. Given that child hypervigilance and hyper-arousal are associated with prenatal stress exposure 9 12 , it follows that prenatal exposure to maternal stress and negative affect may be a risk factor for the development of early sleep problems. Indeed, a small number of studies have begun to provide evidence for this linkage, reporting sleep problems in children prenatally exposed to maternal mood disturbance 13 , 14 and later links to adult insomnia 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Responses of the amygdala to emotional neutral images have been suggested to be exaggerated in patients with posttraumatic stress disorder 61 , 62 . Such responses could be interpreted as the hyperactivation of structures that are involved in responses to neutral stimuli, as a generalized threshold of threatening to non-threatening information processing.…”
Section: Discussionmentioning
confidence: 99%
“… Otte et al (2015) showed in their study that 9-month-old infants of anxious mothers showed stronger reactions to fearful sounds, independently from the emotion of the simultaneously presented visual stimuli. Furthermore, van den Heuvel et al (2018) found that 4-year-olds, prenatally exposed to higher maternal anxiety, exhibited more attention to neutral pictures but not to unpleasant pictures. Correspondingly, maternal mindfulness during pregnancy seems to be associated with 9-month-old infants showing fewer attentional resources to neutral auditory stimuli ( van den Heuvel et al, 2015 ).…”
Section: Introductionmentioning
confidence: 93%
“…Despite the recent good quality studies addressing the relation of prenatal stress and child emotional processing in infancy ( Otte et al, 2015 ; Soe et al, 2016 ; Gustafsson et al, 2018 ; Goodman et al, 2021 ), the association of maternal prenatal stress with toddler’s neural processing of emotional information is unknown. Previous research, to our knowledge, has mainly focused on maternal prenatal anxiety as the indicator of prenatal stress ( Otte et al, 2015 ; van den Heuvel et al, 2018 ). These studies suggest that the association between maternal anxiety and emotional perception of, e.g., fearful sounds and pictures in children.…”
Section: Introductionmentioning
confidence: 99%